The Immunomodulatory Potential of tolDCs Loaded with Heat Shock Proteins - van Eden, Willem; Jansen, Manon A. A.; de Wolf, A Charlotte MT; Ludwig, Irene S.; Leufkens, Paul; Broere, Femke (Frontiers in Immunology, 2017)
Disease suppressive T cell regulation may depend on cognate interactions of regulatory T cells (Tregs) with self-antigens that are abundantly expressed in the inflamed tissues. Heat shock proteins (HSPs) are by their nature up-regulated in stressed cells and therefore abundantly present as potential targets for such regulation. HSP immunizations have led to inhibition of experimentally induced inflammatory conditions in various models. However, re-establishment of tolerance in the presence of an ongoing inflammatory process has remained challenging. Since tolerogenic DCs (tolDCs) have the combined capacity of mitigating antigen-specific inflammatory responses and of endowing T cells with regulatory potential, it seems attractive to combine the anti-inflammatory qualities of tolDCs with those of HSPs.